Запобігання соціальному сирітству шляхом збереження інституту сім'ї в діяльності соціальних служб - Коренських, Марія Володимирівна; Korenskykh, Mariia Volodymyrivna (Національний університет "Львівська політехніка", 2024)
Соціальне сирітство є актуальною проблемою в сучасних умовах війни, адже значна кількість дітей позбавлена батьківського піклування не внаслідок смерті батьків, а в результаті їх соціальної неспроможності, що зумовлена складними життєвими обставинами, алкозалежністю, наркозалежністю, не виконанням батьківських обов'язків, економічними труднощами [1,2]. У цьому контексті важливим є вивчення технологій, які застосовують соціальні служби у підтримці родин, які опинилися у СЖО, зокрема шляхом ведення випадку, розвитку послуги соціального супроводу, впровадження патронатного виховання та взаємодії з територіальними громадами [3]. А також вивчення закордонного досвіду за для покращення надання соціальних послуг сім'ям СЖО. Об’єкт дослідження – соціальне сирітство як соціальна проблема, що постає внаслідок порушення функціонування інституту сім’ї. Предмет дослідження – діяльність соціальних служб щодо запобігання соціальному сирітству шляхом підтримки та збереження сім’ї. Мета роботи – дослідити шляхи запобігання соціального сирітства через ефективне функціонування інституту соціальних служб із зосередженням уваги на збереженні сімейного середовища дитини. Результати дослідження: У першому розділі проаналізовано поняття соціального сирітства, його причини, наслідки та роль сім’ї у соціалізації дитини. У другому – охарактеризовано діяльність соціальних служб, ведення випадку, патронатне виховання, роль громади та зарубіжний досвід запобіганню соціального сирітства. У третьому – представлено результати емпіричного дослідження діяльності центрів соціальних служб та служб у справах дітей на прикладі Львівської області. Виявлено технології, що застосовуються у роботі з даною проблемою та труднощі з якими зіштовхуються фахівці.

Social orphanhood is an urgent problem in the current conditions of war, as a significant number of children are deprived of parental care not because of the death of their parents, but as a result of their social insolvency, which is caused by difficult life circumstances, alcohol and drug addiction, failure to fulfil parental responsibilities, and economic difficulties [1,2]. In this context, it is important to study the technologies used by social services to support families in the situation of VAW, in particular through case management, development of social support services, introduction of foster care and interaction with local communities [3]. The study also aims to learn from international experience in order to improve the provision of social services to families with children in conflict situations. The object of the study is social orphanhood as a social problem that arises as a result of the dysfunction of the family institution. The subject of the study is the activities of social services to prevent social orphanhood by supporting and preserving the family. The purpose of the study is to investigate ways to prevent social orphanhood through the effective functioning of the institution of social services with a focus on preserving the child's family environment. Results of the study: The first section analyses the concept of social orphanhood, its causes, consequences and the role of the family in the child's socialisation. The second section describes the activities of social services, case management, foster care, the role of the community and foreign experience in preventing social orphanhood. The third part presents the results of an empirical study of the activities of centres of social services and services for children on the example of Lviv region. The technologies used in dealing with this problem and the difficulties faced by specialists are identified. Key words: social orphanhood, difficult life circumstances (CLC), centre of social services, service for children, case management, social support, foster care. List of used literature sources. 1. Khokhlov P.A. (2018). Causes and consequences of social orphanhood in modern Ukrainian society. Social prevention of orphanhood, 59-62. 2. Sukhitska, N. V. & Polyhach, H. I. (2023). Social orphanhood as a large-scale problem of the present. Information and its impact on social processes, 236-237. 3. Solianyk, M. G. (2012). Support for families in difficult life circumstances. Collection of scientific works of Kamianets-Podilskyi Ivan Ohienko National University. Series: Social and Pedagogical, (18), 50-56.
Preventing social orphanhood by preserving the family institution in the activities of social services
Keywords: 6.231.00.00; соціальне сирітство; складні життєві обставини (СЖО); центр соціальних служб; служба у справах дітей; ведення випадку; соціальний супровід; патронатне виховання